Analyzing the Problems of Arabic Language Learning in Higher Education - Arifin, Zainul; Lubis, Torkis; Ath-Thukhi, Ahmad Muhammad; Alsokari, Tareq; Ainin, Moh.; Taufan, Muhammad (International Journal of Islamic Studies Higher Education, 2024)
Arabic language learning in higher education has an important role in shaping students' linguistic competence, especially in Islamic-based institutions. However, its implementation in practice often faces challenges that affect the teaching-learning process. This article aims to analyze the problems of Arabic language learning in higher education, identify the source of the problems, and offer solutions to the learning that is carried out. This analysis uses a Systematic Literature Review (SLR) approach by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This article screened 20 articles from Scopus and Google Scholar indexed journals published between 2018-2024. The results of the analysis show that there are four main problems, first the low competence of lecturers in applying learning methods, second the lack of utilization of educational technology in the learning process, third the limitations of teaching materials, fourth the low motivation of students in learning Arabic. These findings indicate that learning Arabic requires new approaches, such as the integration of digital-based technology, continuous training for lecturers, and the provision of teaching materials tailored to the needs and interests of students. The four results of this analysis are expected to provide insights for curriculum development and more effective Arabic learning methods. For future researchers, it is hoped that the results of this analysis can be the main reference and for lecturers, curriculum developers and policy designers in overcoming the challenges of learning Arabic in higher education and improving the quality of graduates who have superior linguistic competence.